The Goose Is (Half) Cooked: a Consideration of the Mechanisms and Interpersonal Context Is Needed to Elucidate the Effects of Personal Financial Incentives on Health Behaviour - Hagger, Martin; Keatley, David; Chan, Derwin; Chatzisarantis, Nikos; Dimmock, J.; Jackson, Ben; Ntoumanis, Nikos (Springer New York LLC, 2014)
While we agree that personal financial incentives (PFIs) may have some utility in public health interventions to motivate people in the uptake and persistence of health behaviour, we disagree with some of the sentiments outlined by Lynagh et al. (Int J Behav Med 20:114–120, 2012). Specifically, we feel that the article gives a much stronger impression that PFIs will likely lead to long-term behaviour change once the incentive has been removed than is warranted by current research. This claim has not received strong empirical support nor is it grounded in psychological theory on the role of incentives and motivation. We also feel that the presentation of some of the tenets of self-determination theory by the authors is misleading. Based on self-determination theory, we propose that PFIs, without sufficient consideration of the mechanisms by which external incentives affect motivation and the interpersonal context in which they are presented, are unlikely to lead to persistence in health behaviour once the incentive is removed. We argue that interventions that adopt PFIs as a strategy to promote health-behaviour change should incorporate strategies in the interpersonal context to minimise the undermining effect of the incentives on intrinsic motivation. Interventions should present incentives as informational regarding individuals’ competence rather than as purely contingent on behavioural engagement and emphasise self-determined reasons for pursuing the behaviour.